A randomized trial comparing the rate of hypoglycemia—assessed using continuous glucose monitoring—in 125 preschool children with type 1 diabetes treated with insulin glargine or NPH insulin (the PRESCHOOL study). Issue 8 (3rd June 2013) - Danne, Thomas; Philotheou, Areti; Goldman, David; Guo, Xiang; Ping, Lin; Cali, Anna; Johnston, Peter
<x xml:space="preserve">Abstract</x> Background Avoidance of hypoglycemia is a key consideration in treating young children with type 1 diabetes (T1DM). Key Objective To evaluate hypoglycemia with insulin glargine vs. neutral protamine Hagedorn (NPH) insulin in young children, using continuous glucose monitoring (CGM). Subjects Children of 1 to <6 yr treated with once‐daily glargine vs. once‐ or twice‐daily NPH, with bolus insulin lispro/regular human insulin provided to all. Methods Twenty‐four week, multicenter, randomized, open‐label study. Primary endpoint was event rate of composite hypoglycemia [symptomatic hypoglycemia, low CGM excursions (<3.9 mmol/L) or low fingerstick blood glucose (FSBG; <3.9 mmol/L)]. Noninferiority of glargine vs. NPH was assessed for the primary endpoint. Results One hundred and twenty‐five patients (mean age, 4.2 yr) were randomized to treatment (glargine, n = 61; NPH, n = 64). At baseline, mean HbA1c was 8.0 and 8.2% with glargine and NPH, respectively. Composite hypoglycemia episodes/100 patient‐yr was 1.93 for glargine and 1.69 for NPH; glargine noninferiority was not met. Events/100 patient‐yr of symptomatic hypoglycemia were 0.26 for glargine vs. 0.33 for NPH; low CGM excursions 0.75 vs. 0.72; and low FSBG 1.93 vs.1.68. There was a slight difference in between‐group severe/nocturnal/severe nocturnal hypoglycemia and glycemic control. All glargine‐treated patients received once‐daily injections; on most study days NPH‐treated patients received twice‐daily injections. Conclusions While glargine noninferiority was not achieved, in young children with T1DM, there was a slight difference in hypoglycemia outcomes and glycemic control between glargine and NPH. Once‐daily glargine may therefore be a feasible alternative basal insulin in young populations, in whom administering injections can be problematic.